2018
DOI: 10.3390/app9010087
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Thermal Conductivity and Effective Parameters

Abstract: Due to the more powerful and miniaturized nature of modern devices, conventional heat-transfer working fluids are not capable of meeting the cooling needs of these systems. Therefore, it is necessary to improve the heat-transfer abilities of commonly used cooling fluids. Recently, nanoparticles with different characteristics have been introduced to base liquids to enhance the overall thermal conductivity. This paper studies the influence of various parameters, including base liquid, temperature, nanoparticle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 85 publications
(364 reference statements)
1
27
0
Order By: Relevance
“…The negatively charged head of SDS could change the surface charges of Al 2 O 3 and form repulsion forces among the nanoparticles. The agglomeration of nanoparticles therefore could be minimized by the act of the repulsion forces and lead to the improvements of the PDIVs for RBDPO, CO and MO [ 47 ]. Moreover, it is found that the differences on the nanoparticles dispersion between with and without SDS are not significant to cause agglomeration based on FTIR and particle size distribution [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negatively charged head of SDS could change the surface charges of Al 2 O 3 and form repulsion forces among the nanoparticles. The agglomeration of nanoparticles therefore could be minimized by the act of the repulsion forces and lead to the improvements of the PDIVs for RBDPO, CO and MO [ 47 ]. Moreover, it is found that the differences on the nanoparticles dispersion between with and without SDS are not significant to cause agglomeration based on FTIR and particle size distribution [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thermal conductivity measurements and the thermal conductivity ratio of In an attempt to understand the phenomena that could be responsible of such thermal conductivity enhancement, some models from the literature are considered in the following [36][37][38][39][40][41][42]. Many complex and possibly coupled mechanisms shown in Figure 10have been considered in the past to use or develop theoretical models for thermal conductivity of nanofluids such as classical effective theory, nanoscale layer, agglomeration and J o u r n a l P r e -p r o o f aggregation, Brownian motion, etc [38,43].…”
Section: Thermal Conductivity Of Nanofluidsmentioning
confidence: 99%
“…Apart from the apparent dynamic viscosity, the strain oscillation already displayed the viscoelastic nature of NFs. Therefore, to estimate the yield stress Herschel Bulkley (H-B) 64 and Bingham models 65 were fitted to the shear flow experimental data as shown in Equations (1) and 2, respectively.…”
Section: Shear Flow Behaviourmentioning
confidence: 99%
“…For the conventional heat transfer fluids (HTFs), thermal conductivity and the rheology are key parameters which can affect the FTSs efficiency. Since the development of nanofluids (NFs), a variety of nanoparticles (NPs) with a wide range of size, morphology and exotic thermal properties have been used as the dispersed phase in conventional HTFs 1 . Additionally, the researchers have also exploited the potential of nanocomposites materials to improve the heat transfer (HT) performance of carrier fluids 2 .…”
Section: Introductionmentioning
confidence: 99%